2022
DOI: 10.1016/j.micpath.2022.105404
|View full text |Cite
|
Sign up to set email alerts
|

Genomic characterization unravelling the causative role of SARS-CoV-2 Delta variant of lineage B.1.617.2 in 2nd wave of COVID-19 pandemic in Chhattisgarh, India

Abstract: COVID-19 pandemic 2nd wave catastrophic effect in the state of Chhattisgarh, India, from where no exclusive genomic data yet published, has prompted us to undertake this study to unearth the causative variant. Whole-genome sequencing of SARS-CoV-2 isolated from COVID-19 infected nine vaccinated healthcare workers (HCW), thirty mild/moderate, seventeen severe, and twenty-seven deceased patients, was performed. The significant predominance of the SARS-CoV-2 variant of concern (VOC), Delta (lineage B.1.617.2) ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 32 publications
2
17
0
Order By: Relevance
“…The role of each specific mutation has not been completely elucidated, but they have all been implicated in immune escape [36][37][38]. In addition, the mutation S:A222V, present in AY.26, slightly increases human cell receptor (ACE2) binding [39], while the mutations N:R203M, common to the three sublineages, and N:G215C, present in AY.20 and AY.100, have been shown to improve viral replication and assembly [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…The role of each specific mutation has not been completely elucidated, but they have all been implicated in immune escape [36][37][38]. In addition, the mutation S:A222V, present in AY.26, slightly increases human cell receptor (ACE2) binding [39], while the mutations N:R203M, common to the three sublineages, and N:G215C, present in AY.20 and AY.100, have been shown to improve viral replication and assembly [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly found Delta mutations seen in our sequences were T19R, G142D, ΔE156/F157, R158G, L452R, T478K, D614G, P681R, and D950N ( Figure 3 and Figure 4 ). T19R, G142D, ΔE156/F157 and R158G are located within the antigenic supersite of the S protein NTD and affect immune evasion [ 96 , 97 ]. Furthermore, ΔE156/F157 and R158G contribute to increased infectivity [ 98 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study identified the predominance of BA.2 and its sub-lineage (93.5%) followed by BA.5.2 and its sub-lineage BA. 5 11). An earlier study from Denmark and India has reasoned a higher fusogenicity and reproduction number (R0) of 2.445 for BA.2 predominance (12).…”
Section: Discussionmentioning
confidence: 99%